2023
DOI: 10.3390/life13030802
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Potential of Ethyl Acetate Extract of Marine Bacteria Pseudomonas aeruginosa Strain RLimb

Abstract: Biofouling is defined as the excessive colonization process of epibiotic organisms, ranging from microfoulers to macrofoulers, on any submerged surface in water. Previous research has attempted to explore the antifouling activity of bacterial isolates due to the biofouling problems occurring worldwide. One solution is to inhibit the early stage of fouling using secondary metabolites produced by marine bacteria. This study aims to determine the antifouling activities of the marine microorganism P. aeruginosa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It showed that the bacterial extracts did not affect the ability to inhibit the bacterial biofilm formation. 48 The present study focuses on the potential of LAB, isolated from the mentioned lichen species, to synthesize novel compounds with antifungal, antimicrobial, and enzymatic properties, addressing the significant issue of biofouling in the marine industry. Lichen symbiotic associations showed promising effects in producing antimicrobial and antifouling compounds and are engaged in various functions.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that the bacterial extracts did not affect the ability to inhibit the bacterial biofilm formation. 48 The present study focuses on the potential of LAB, isolated from the mentioned lichen species, to synthesize novel compounds with antifungal, antimicrobial, and enzymatic properties, addressing the significant issue of biofouling in the marine industry. Lichen symbiotic associations showed promising effects in producing antimicrobial and antifouling compounds and are engaged in various functions.…”
Section: Discussionmentioning
confidence: 99%